ENHANCING THE METHODOLOGY OF TEACHING THE PHYSICS COURSE THROUGH INTERDISCIPLINARY INTEGRATION (A CASE STUDY OF GRADE 7) - Boyturayeva Gulbaxor Kamoliddin qizi (Bright Mind Publishing, 2025)
This article explores the principles, goals, and significance of interdisciplinary teaching in the context of school physics education. It presents a methodological framework for integrating interdisciplinary connections into the Grade 7 physics curriculum and offers practical recommendations for educators.
Keywords: Interdisciplinary teaching, physics education, educational methodology, cognitive skills, pedagogical strategies.